FORM OF LAYING HENS EGGS IN THE FUNCTION OF DIFFERENT LAMPS USED IN PRODUCTION - Pereira,Danilo F. (2017)
ABSTRACT: Lighting, either in its intensity or in its luminous spectrum, affects the eggs quality. This study evaluated the effect of four lamps (sodium vapor lamp, mercury vapor lamp, fluorescent lamp and incandescent lamp) that have different luminous spectra in the form of commercial poultry eggs. For this, 60 laying hens of the same age were separated for 63 days in four aviaries with reduced and distorted scale. In each treatment, different lamps were installed which provided similar luminous intensities. At the end of the period, these eggs were taken as samples for the fluorescent, incandescent, mercury vapor and sodium vapor lamps. In this way, images were made of these eggs, using a camera installed on a fixed tripod on a flat table with black background. In a room with controlled lighting, ensuring the same distance and angle for all eggs. The Matlab® program was used to perform the image analysis, recording measurements of area, perimeter and minimum and maximum distances of the mass center of each egg. The measurements were grouped by treatment and the Tukey's test of averages was applied. The results showed that the eggs removed from the sodium vapor treatment presented a more elongated shape. It is concluded that the light spectrum of the lamps affects the shape of the eggs and this should be considered in the planning of lighting programs in aviaries.